An insight into the microstructures and composition of 2,700 m-depth deep-sea limpet shells - Ying, Zhehan; Wang, Shi; Wong, Wai Chuen; Cai, Xiangbin; Feng, Xuemeng; Xiang, Shengling; Cai, Yuan; Qian, Pei-Yuan; Wang, Ning (Frontiers in Marine Science, 2022)
Structural and physiochemical properties contribute to biological adaptation of deep-sea animals to their harsh living environment but have hardly been investigated systematically. In the present study, we for the first time applied various materials characterization techniques including transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), Fourier-transform infrared (FT-IR) spectroscopy to investigate the shell microstructures and chemical composition of a deep-sea limpet Eulepetopsis crystallina collected from the Tiancheng hydrothermal vent field at a depth of around 2,700m in the Southwest Indian Ocean. Analyses of shell microstructural morphology and diffraction patterns of E. crystallina explicitly revealed the layered structures, exfoliation characteristics and crystallographic orientation of each layer’s unit cell which was tilted at a small angle sequentially. In comparison with ordinary shallow-water limpet Cellana Toreuma shells, E. crystallina shells showed unique chemical composition and contained pure calcite of calcium carbonate polymorph and the trace of phosphate originated from regional phosphatic sediments of the Southwest Indian Ocean. The further microscopic analyses indicated that the shell of the deep-sea limpet E. crystallina features integrated and untruncated layer structures with a compressed width, possibly owning to the ultra-high hydrostatic pressure, which confirmed effects of the living environment on the shell microstructure of deep-sea animals.